Increasing Student Activity Using The TSTS Learning Model Assisted By Digital Comics Media - Dhuwik Afriliani; Mukhamad Murdiono; Muhamad Akbar Hajuan (AL-ISHLAH: Jurnal Pendidikan, 2022)
One of the important components that need to be developed to achieve the goals of Pancasila and Citizenship Education (PPKn) is to create citizens who are able to actively participate. However, in PPKn learning, there are still many teachers who use the lecture method, so they are not able to stimulate the active involvement of students. This study aims to increase the activity of students using the Two Stay Two Stray (TSTS) learning model assisted by digital comic media by involving students in class XI IPA-4 SMA Negeri 1 Kandangan. The method used in this research is classroom action research which is carried out in two cycles. Data was collected through observation and interviews. Data analysis techniques include data reduction, descriptive presentation, and conclusions. The main finding in this study was that there was an increase in student activity from low (average percentage 41.53%) to high (average percentage 82.89%). Based on these findings, it can be concluded that the TSTS learning model assisted by digital comics can increase the activeness of students in Civics learning.